D‐mannose alleviates osteoarthritis progression by inhibiting chondrocyte ferroptosis in a HIF‐2α‐dependent manner. (25th September 2021) - Zhou, Xueman; Zheng, Yingcheng; Sun, Wentian; Zhang, Zhenzhen; Liu, Jiaqi; Yang, Wenke; Yuan, Wenxiu; Yi, Yating; Wang, Jun; Liu, Jin
Abstract: Objectives: Chondrocyte ferroptosis contributes to osteoarthritis (OA) progression, and D‐mannose shows therapeutic value in many inflammatory conditions. Here, we investigated whether D‐mannose interferes in chondrocyte ferroptotic cell death during osteoarthritic cartilage degeneration. Materials and methods: In vivo anterior cruciate ligament transection (ACLT)‐induced OA mouse model and an in vitro study of chondrocytes in an OA microenvironment induced by interleukin‐1β (IL‐1β) exposure were employed. Combined with Epas1 gene gain‐ and loss‐of‐function, histology, immunofluorescence, quantitative RT‐PCR, Western blot, cell viability and flow cytometry experiments were performed to evaluate the chondroprotective effects of D‐mannose in OA progression and the role of hypoxia‐inducible factor 2 alpha (HIF‐2 α) in D‐mannose‐induced ferroptosis resistance of chondrocytes. Results: D‐mannose exerted a chondroprotective effect by attenuating the sensitivity of chondrocytes to ferroptosis and alleviated OA progression. HIF‐2α was identified as a central mediator in D‐mannose‐induced ferroptosis resistance of chondrocytes. Furthermore, overexpression of HIF‐2α in chondrocytes by Ad‐ Epas1 intra‐articular injection abolished the chondroprotective effect of D‐mannose during OA progression and eliminated the role of D‐mannose as a ferroptosis suppressor. Conclusions: D‐mannose alleviates osteoarthritis progression by suppressing HIF‐2α‐mediated chondrocyte sensitivity to ferroptosis, indicating D‐mannose to be a potential therapeutic strategy for ferroptosis‐related diseases. Abstract : D‐Mannose effectively alleviates osteoarthritis progression by suppressing cartilage degeneration. D‐mannose protects osteoarthritic chondrocytes by attenuating sensitivity to ferroptosis. HIF‐2α is vital in potentiating the susceptibility of chondrocytes to ferroptosis. HIF‐2α is a central mediator in D‐mannose‐induced ferroptosis resistance.